PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELAUI DISCOVERY LEARNING, PROBLEM BASED LEARNING, DAN PROJECT BASED LEARNING - M. Holil (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
Briefly, Moslem world has been left behind in many aspects, politic, economy, education, more over sciences and technology. One of the ways out proposed by contemporal Muslim Thinkers, such as Naquib al-Attas and Islamail Raji al-Faruqi, is that Muslim should integrate empirical and religous science. The Integration aims at elimanating the dichotomy between empirical and religous sciences, so that Muslim can develope the two sciences as well as build both rational and religous community as Islamic civilization reached in the past. To achieve the civilized muslim, this idea must be implemented soon in education, especially in teaching muslim students. Hence, this article specifically offered technical methods in teaching religous sciences by occupying scientific approach through three various models of learning, discovery learning, problem based learning and project based learning.